War at Home: Violence and Domestic Space in Tomar tu mano (2021), by Claudia Hernández - Rojas González, José Pablo (2024)
From the idea of the domestic space as an apprehending space, the article aims to reflect on the forms of violence that, in the novel Tomar tu mano (2021), by Claudia Hernández, the represented female subjects experience. The domestic space, in the case of this literary text, seems to be formed as an extension of the scope of war and its logic of domination, which, consequently, affects the female protagonists in their own bodies, often controlled by the designs of the male subjects with whom they relate and with whom they form families. Thus, the domestic space exposed in the text will be analyzed and understood as a regime that oppresses women to the point of condemning them to a subordinate life. Finally, the domestic space is, in Hernández’s work, a kind of “social verdict”, covered by emotions such as love or happiness, which function as a patriarchal trap.